32 Congenital Arteriovenous Malformation of The Breast Associated with Giant Hairy Naevus: A Case Report. (12th October 2021) - O'Beirn, E; Elliott, J; Neary, C; McLaughlin, R
Abstract: Introduction: An arteriovenous malformation (AVM) is defined as an abnormal connection between arteries and veins, bypassing the capillary system. AVM of the breast is a rare clinical entity, with limited evidence to guide management. We present the case of a congenital AVM of the breast in an otherwise healthy woman, with an interesting presenting complaint. Case Description: A 38-year-old female presented with a 'buzzing' sensation and mastalgia in her left breast. Examination revealed a visible pulsatile linear abnormality with a bruit on auscultation. Duplex ultrasonography demonstrated mixing of the arterial and venous flow, consistent with an AVM. Operative management entailed ultrasound guided identification, ligation and excision of all aneurysmal segments. Histopathologic evaluation demonstrated an AVM with no malignant features. At one year postoperatively, the patient reported complete symptom resolution. Literature review identified nine case reports, including two cases of congenital breast AVM, both treated surgically. Seven cases of iatrogenic AVM were identified, with diagnosis based on duplex ultrasonography and management by surgical ligation in all except one, which resolved spontaneously. Conclusions: ongenital AVM of the breast is a rare clinical entity. Diagnosis can be established using duplex ultrasonography, while CT and MRI may be useful for preoperative planning. Endovascular management alone is associated with high recurrence rates and surgical excision is the favoured approach where technically feasible without major aesthetic or functional compromise.